The Discovery of a 41 s Radio Pulsar PSR J0311+1402 with ASKAP - Wang, Y.; Uttarkar, P.A.; Shannon, R.M.; Lee, Y.W.J.; Dobie, D.; Wang, Andy; Bannister, K.W.; Caleb, M.; Deller, A.T.; Glowacki, Marcin; Jahns-Schindler, J.N.; Murphy, T.; et al. (2025)
The emerging population of long-period radio transients (LPTs) shows both similarities and differences with normal pulsars. A key difference is that their radio emission is too bright to be powered solely by rotational energy. Various models have been proposed (including both white dwarf or neutron star origins), and their nature remains uncertain. Known LPTs have minutes-to-hours-long spin periods, while normal pulsars have periods ranging from milliseconds to seconds. Here, we report the discovery of PSR J0311+1402, an object with an intermediate spin period of 41 s, bridging the gap between LPTs and normal pulsars. PSR J0311+1402 exhibits low linear (∼25%) and circular polarization (∼5%) and a relatively steep spectral index (∼ −2.3), features similar to normal pulsars. However, its observed spin-down properties place it below the pulsar death line, where pair production and thus radio emission are expected to cease. The discovery of PSR J0311+1402 suggests the existence of a previously undetected population within this intermediate period range, presumably missed due to selection biases in traditional pulsar search methods. Finding more such objects is important to fill the current gap in neutron star spin periods, improving our understanding of the relationships among rotation-powered pulsars and LPTs.